Effect of 12 weeks of wrist and forearm training on high school baseball players - Szymanski, D. J.; Szymanski, J. M.; Molloy, J. M.; Pascoe, D. D. (The Journal of Strength and Conditioning Research, 2004)
This study examined the effect of 12 weeks of wrist and forearm training on male high school baseball players (mean age = 15.3 ± 1.1 years). Participants (N = 43) were tested for 10 repetition maximum (RM) wrist barbell flexion, wrist barbell extension, dominant (D) and nondominant (ND) hand-forearm supination, D and ND forearm pronation, D and ND wrist radial deviation, D and ND wrist ulnar deviation, D and ND grip strength, and a 3RM parallel squat (PS) and bench press (BP). Group 1 (n = 23) and group 2 (n = 20), randomly assigned by a stratified sampling technique, performed the same resistance exercises while training 3 days a week for 12 weeks according to a stepwise periodized model. Group 2 also performed wrist and forearm exercises 3 days a week for 12 weeks to determine if additional wrist and forearm training provided further wrist and forearm strength improvements. All wrist and forearm strength variables were measured before and after 12 weeks of training. The 3RM PS and BP were measured at 0 and after 4, 8, and 12 weeks of training. Both groups significantly increased wrist and forearm strength (kg ± SD) except 10RM D and ND forearm supination for group 1 (p < 0.05). Group 2 showed statistically greater improvements (p < 0.05) in all wrist and forearm strength variables than did group 1 except for D and ND grip strength. Predicted 1RM (kg ± SD) PS and BP increased significantly (p < 0.05) after weeks 4, 8, and 12 for both groups. These data indicate that a 12-week stepwise periodized training program can significantly increase wrist, forearm, PS, and BP strength for both groups. Additionally, group 2 had further wrist and forearm strength gains.